2015
DOI: 10.5139/ijass.2015.16.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Rotor Blade Sweep Effect on the Performance of a Small Axial Supersonic Impulse Turbine

Abstract: In this paper, a computational study was conducted in order to investigate the rotor blade sweep effect on the aerodynamics of a small axial supersonic impulse turbine stage. For this purpose, three-dimensional unsteady RANS simulations have been performed with three different rotor blade sweep angles (-15°, 0°, +15°) and the results were compared with each other. Both NTG (No tip gap) and WTG (With tip gap) models were applied to examine the effect on tip leakage flow. As a result of the simulation, the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In 2015, Neshat et al [19] investigated the simultaneous effects of the sweep and lean of the blades in one stage of a transonic compressor on its performance. The numerical results indicated that the backward sweep rotor blade increased the stage efficiency by 0.5% at design conditions, while the stall margin reduces, and the chocking mass flow rate diminished by 1.5%.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…In 2015, Neshat et al [19] investigated the simultaneous effects of the sweep and lean of the blades in one stage of a transonic compressor on its performance. The numerical results indicated that the backward sweep rotor blade increased the stage efficiency by 0.5% at design conditions, while the stall margin reduces, and the chocking mass flow rate diminished by 1.5%.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Pullan and Harvey (2008) and Yoon et al (2014) achieved the same results for axial flow turbines. Jeong et al (2015) numerically showed that backward sweep provided up to 1% efficiency increasing compared with the baseline. However, preliminary results obtained in the previous part of the paper did not show any positive effect of a backward sweep for the axial impulse turbine with axisymmetric nozzles.…”
Section: Introductionmentioning
confidence: 98%